2020
DOI: 10.1177/2042018820943374
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control achievement in a population with premature coronary artery disease: results of the genetics of atherosclerotic disease study

Abstract: Background and aims: To the best of our knowledge, no studies have investigated the metabolic control of patients with premature coronary artery disease (CAD). The present study analyzes the metabolic control, defined as the simultaneous target in blood pressure, low-density lipoprotein cholesterol, non-high-density lipoprotein cholesterol and hemoglobin A1c, as well as the factors associated with its achievement in patients with premature CAD. Methods: The study included 1206 patients with CAD diagnosed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…On the other hand diabetes, hypertension, dyslipidemia and smoking are key risk factors for CVD [ 4 , 5 , 6 ]. In fact, people with both diabetes and hypertension have a four-fold increased risk for the development of CVD and substantially higher risk of CVD death and all-cause mortality [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand diabetes, hypertension, dyslipidemia and smoking are key risk factors for CVD [ 4 , 5 , 6 ]. In fact, people with both diabetes and hypertension have a four-fold increased risk for the development of CVD and substantially higher risk of CVD death and all-cause mortality [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients normalizing blood sugar, the control of dyslipidemia, and reduction of blood pressure are the primary targets to improve life quality, to delay the progression to CKD, and prevent cardiovascular complications [ 1 , 2 , 3 , 5 ]. However, these actions do not prevent the progression to ESRD.…”
Section: Introductionmentioning
confidence: 99%
“… 32 Smoking status was defined as current if the subject self-reported that have smoked any tobacco in the previous 12 months and included those who had quit a year earlier; non-smokers were defined as those who have more than 1 year without smoking or who have never smoked. 33 None of the participants were taking any antioxidant or vitamin supplement.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were categorized according to the KDIGO classification into six stages (G1, G2, G3a, G3b, G4, and G5). 33 Descriptive statistics were used to estimate means and standard deviation for normally distributed variables, and median and interquartile range for variables with skewed distribution. Frequencies were expressed in percentages.…”
Section: Methodsmentioning
confidence: 99%
“…Debido a que las ECV representan una de las principales causas de mortalidad en el mundo, causando erogaciones financieras importantes por el tratamiento a corto, mediano y largo plazo, la prevención y el tratamiento se enfocan principalmente en el control de los factores de riesgo 10,11 . En general, el tratamiento de los pacientes con ECV combina intervención farmacológica y modificación del estilo de vida 9,12 . En este contexto, varios estudios preclínicos y clínicos demuestran que la ingesta de alimentos de origen vegetal, como frutas, semillas y especias, aportan elementos cardioprotectores, ya que son ricos en compuestos con actividad biológica benéfica 13 .…”
Section: Enfermedad Cardiovascularunclassified